Proses Pembelajaran Tari Badaya dalam Kegiatan Ekstrakurikuler di SMP Negeri 2 Jatiwangi - Lulu Hana Huwaida; Rimasari Pramesti Putri (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
This study examines the learning process of Badaya dance in extracurricular activities at SMP Negeri 2 Jatiwangi. Badaya dance depicts noble dancers welcoming guests, functioning as a welcoming dance in the official celebration of the Sundanese Mapag Panganten tradition. This study aims to analyze and describe the learning process of Badaya Dance, with a focus on learning objectives, learning materials, learning methods, learning tools and learning evaluations applied. This study uses a qualitative approach, involving participatory observation techniques, in-depth interviews, and document analysis to collect in-depth and comprehensive data. The results show that learning is carried out in a scheduled and intensive manner by utilizing the volleyball court area as the activity center. Field findings indicate that the dance team of SMP Negeri 2 Jatiwangi has the ability to adapt dynamic formations, ranging from solo performances to complete formations (involving lengser, ambu, ponggawa, and umbrella holders) according to the context of events such as welcoming guests, art performances, and student graduation. Overall, this extracurricular activity is effective in developing students' characters who are confident and culturally insightful, while also being a representative medium in maintaining the existence of Sundanese traditional arts in the school environment.